2017
DOI: 10.4103/jovr.jovr_66_16
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sub-Tenon's bupivacaine on oculocardiac reflex during strabismus surgery and postoperative pain: A randomized clinical trial

Abstract: Purpose:Oculocardiac reflex (OCR), defined as bradycardia induced by manipulation of extraocular muscles, is a serious complication during strabismus surgery for which prevention and proper management is required. In the present study, we investigated the efficacy of sub-Tenon injection of bupivacaine for prevention of OCR and postoperative pain.Methods:A prospective randomized controlled clinical trial was conducted. Fifty patients who were candidates for strabismus surgery were randomized into case (sub-Teno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The current study revealed that PBA and STA provided the best safety profile with no recorded cases of OCR or postoperative nausea and vomiting. In agreement with this finding, Talebnejad et al [26] concluded that sub-Tenon injection of bupivacaine as a local anesthetic significantly prevented OCR and decreased the severity of bradycardia in pediatric patients who underwent strabismus surgery.…”
Section: Discussionmentioning
confidence: 56%
“…The current study revealed that PBA and STA provided the best safety profile with no recorded cases of OCR or postoperative nausea and vomiting. In agreement with this finding, Talebnejad et al [26] concluded that sub-Tenon injection of bupivacaine as a local anesthetic significantly prevented OCR and decreased the severity of bradycardia in pediatric patients who underwent strabismus surgery.…”
Section: Discussionmentioning
confidence: 56%
“…This study also shows that sub-tenon's injection of bupivacaine is associated with decreased postoperative pain. 16 Varposhti et al compared the effect of Tetracaine topical eye drops with placebo and found the incidence and severity of oculocardiac reflex was more in placebo group during the muscle cutting phase of the surgery but there was no difference between the two during the muscle release stage. 13 In our study we did not sub classify the results in to release and cutting phase.…”
Section: Resultsmentioning
confidence: 99%
“…15 One of the options is to give sub-tenon's injection of bupivacaine after the induction of general anaesthesia to prevent the occurrence of oculocardiac reflex. 4,16,17 Talebnejad et al reported 32% incidence of oculocardiac reflex in sub-tenon's group versus 100% in control group who received no injection (p=0.002) which is statistically significant reduction. 16 similarly, Bakr et al reported incidence of oculocardiac reflex in 18% of patients versus 38% in those who received placebo (0.9% normal saline) injections (p=0.003) which is statistically significant.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation